Capturing the Invisible Beauty: Schlieren Imaging Technology Reveals the Secrets of Gas Flow - Li, Yuhong (Transactions on Computer Science and Intelligent Systems Research, 2025)
Schlieren imaging technology is a magical tool that can "see" air and temperature fluctuations. Schlieren imaging technology uses the refraction of light to convert tiny changes in fluid substances into visual images, making invisible physical phenomena intuitive and easy to understand. High-end Schlieren imaging systems offered by companies like Holmarc, are designed for advanced applications and come with sophisticated features. These systems can be quite expensive, often costing several thousand dollars, making them less accessible for educational institutions, hobbyists, or researchers with limited budgets. In this project, we designed and constructed an affordable custom Schlieren imaging system utilizing a concave mirror, a point light source, and a knife-edge filter. The system was used to investigate various thermal and aerodynamic phenomena by introducing different heat sources and airflow disruptions. Experiments using hot water, a hair dryer, and a candle flame produced distinct Schlieren patterns: the candle flame exhibited a well-defined transition from laminar to turbulent flow, the hair dryer demonstrated contrasting temperature fluctuations, and hot water vapor diffusion demonstrated clear turbulent thermal plume dynamics. These experiments highlight the system’s capability to resolve complex relationships between airflow velocity and heat transfer. In the hair dryer experiment, the speed and temperature of the airflow were vividly captured in the images, helping us better understand the complex relationship between wind speed and heat conduction. One of the most striking results was the imaging of the candle flame. The Schlieren diagram not only revealed the shape of the flame but also visualized the surrounding heat flow dynamics and temperature gradients, illustrating the transition from laminar to turbulent flow. This project demonstrates the great potential of custom Schlieren imaging technology in thermal and fluid mechanics research, providing us with a new visual language to uncover the physical mysteries behind these seemingly ordinary phenomena by "seeing" temperature and airflow. This research has opened up an unprecedented perspective for dynamic monitoring of heat sources and analysis of air flow, and provides more possibilities for future scientific exploration.